Eco-Ontology for supporting Interoperability in Product Life Cycle within Product Sustainability - Mohammed, Moseed; Awanis, Romli; Noormazlinah, Ahmad (IOP Publishing, 2021)
Ontology originated in a branch of artificial intelligence and widely used in various fields such as semantic web, engineering systems, software engineering, biomedical informatics, library science, information engineering, knowledge management, decision-making system, and the industry sector. Ontology supports the knowledge management system and helps get significant features of product design. The lack of using knowledge is the critical challenge in information interoperability of the manufacture, especially, in the early stage of design. This information must be gathered, stored, shared, reused, and managed in a consistent and standardized way. The aim of this study is to use the ontology for reducing the complexity of information and increasing its organization, facilitating sharing and reusing of information, and improving its accuracy. The use of ontology has shown optimistic results to support comprehensive decisions in the industrial field. The researchers have confirmed the importance of using the ontology to improve interoperability over the product life cycle and address the impacts of products through the outputs of the product life cycle assessment tool. This study is expected to contribute to develop an efficient and practicable sustainability tool during product design with a complete view to solve the lack of sharing information in the product life cycle, provide high quality and comprehensive recommendations to support the manufacturing processes for product sustainability.